Enhancing Elementary Science Learning Through Jigsaw Cooperative Learning: A Classroom Action Research - Syabina Nurfadila; Nashrullah Nashrullah; Muslim AR Muslim AR; Arif Firmansyah; Muhammad Nazimuddin Al Kamil; Surahman Wilade (Papanda Publisher, 2026)
Despite progressive curriculum reforms emphasizing student-centered learning in Indonesia's Kurikulum Merdeka, elementary IPAS instruction remains predominantly teacher-centered, limiting student engagement and conceptual understanding. This classroom action research employed Kemmis and McTaggart's cyclical model across two intervention cycles with 28 Grade IV students at SD Inpres Perumnas Palu. Data were collected through achievement tests, structured observations of teacher and student activities, and field documentation. Analysis integrated quantitative measures of learning mastery with qualitative assessment of instructional processes using Miles and Huberman's framework. Classical mastery remained stable between pre-action baseline (28.57%) and Cycle I (28.57%), indicating that procedural implementation alone proved insufficient. Following targeted refinements in Cycle II—including enhanced scaffolding, systematic group monitoring, and explicit instructional guidance—classical mastery increased dramatically to 85.71%, surpassing the 80% success criterion. Student activity improved from 58% to 69.5%, while teacher activity increased from 55% to 68%. Findings demonstrate that Jigsaw cooperative learning effectiveness depends critically on implementation quality rather than structural arrangements alone. Results align with constructivist and sociocultural learning theories, particularly Vygotsky's Zone of Proximal Development, confirming that appropriately scaffolded peer interaction enables students to achieve understanding beyond independent capabilities. The study extends predominantly Western cooperative learning scholarship into Indonesian elementary contexts, providing empirical evidence for pedagogically thoughtful implementation strategies.